The Trouble With Binaries: A Perspective on the Science of Reading. (19th April 2021) - Yaden, David B.; Reinking, David; Smagorinsky, Peter
ABSTRACT: In this article, we critique the science of reading when it is positioned within the reading wars as settling disagreements about reading and how it should be taught. We frame our argument in terms of troublesome binaries, specifically between nature and nurture. We interpret that binary in relation to Overton's distinction between split and relational metatheories, with the latter suggesting a more integrative view of nature and nurture. Focusing on the nature side of the binary, which predominates when the science of reading is promoted in the reading wars, we argue that its singular focus limits the range of scientific inquiry, interpretation, and application to practice. Specifically, we address limitations of the science of reading as characterized by a narrow theoretical lens, an abstracted empiricism, and uncritical inductive generalizations derived from brain‐imaging and eye movement data sources. Finally, we call for a relational metatheoretical stance and offer emulative examples of that stance in the field.